A comparison of the health and environmental impacts of increasing urban density against increasing propensity to walk and cycle in Nashville, USA. Issue 1 (2nd January 2020) - Ahmad, Sohail; Goodman, Anna; Creutzig, Felix; Woodcock, James; Tainio, Marko
ABSTRACT: The transportation sector accounts for approximately 23% of the total energy-related carbon dioxide (CO2 ) emissions worldwide and 33% in the USA. At the same time, physical inactivity contributes to adverse health through non-communicable diseases. If policies can increase active transport (walking and cycling) and reduce car use, they could benefit human health and environmental health but the relative impact of different approaches has been under researched. This study estimated change in all-cause mortality and CO2 emissions in greater Nashville, Tennessee (USA) for two scenarios: (a) the propensity to walk and cycle a trip of a given distance increases directly to the same levels as seen in England, and (b) walking and cycling trips increase and travel distance decrease indirectly as a result of a more compact urban form. If the propensity to walk and cycle in Nashville were equal with England, about 339 deaths and about 36 ktCO2 e (1%) of transportation-related CO2 emissions could be avoided per year. The compact urban form scenario could avoid 170 deaths and 370 ktCO2 e (10%) of transportation-related CO2 emissions. In Nashville, both increasing the propensity to use active transport and more compact urban form would have notable public health gains, but a more compact form would have a much bigger effect on emissions.